Involution of Community Empowerment in Strengthening the Household Economy of Homeless and Beggars in Topeng Village, Malang City - Aji, Anggraito Wisnu; Susilo, Rachmad Kristiono Dwi; Kusumastuti, Frida (Jurnal Sosiologi Pendidikan Humanis, 2023)
One of the problems in Malang City is that there are still marginalized groups such as homeless people and beggars. Through the Desaku Menanti program initiated by the Ministry of Social Affairs and managed by the Malang City P3AP2KB Social Service, they are placed in Kampung Topeng to be empowered. This coaching has been going on for 4 years (starting from 2016 to 2020). However, in 2019 this area had no productive activities or an involution process occurred. This research uses a qualitative approach with ethnography. With the AGIL scheme (Adaptation, Goal-attainment, Integration, Latency) which is part of Talcott Parsons' Functional Structural Theory, this research produced several findings. Based on data collection about homeless people and beggars in Kampung Topeng. The findings of this study state that the form of empowerment involution is in the form of program unsustainability. The factors causing involution come from program implementation and target beneficiaries. From the program implementer's side, it is closely related to changes in the priority scale of the agency's program, changes in the head of the agency, limited resources, deterioration of collaboration, the issue of location far from the city center. Meanwhile, from the community side, the culture of poverty and non-standardized quality. Involusi Pemberdayaan Masyarakat dalam Penguatan Ekonomi Rumah Tangga Gelandangan dan Pengemis di Kampung Topeng, Kota MalangSalah satu permasalahan di Kota Malang adalah masih terdapat kelompok marginal seperti gelandangan dan pengemis. Melalui program Desaku Menanti yang digagas oleh Kementerian Sosial dan dikelola oleh Dinas Sosial P3AP2KB Kota Malang mereka ditempatkan di Kampung Topeng untuk diberdayakan. Pembinaan ini sudah berlangsung selama 4 tahun (mulai dari tahun 2016 sampai 2020). Namun pada 2019 kawasan ini tidak ada aktivitas yang produktif atau  terjadi proses involusi. Penelitian ini menggunakan pendekatan kualitatif dengan jenis etnografi. Dengan skema AGIL (Adaptation, Goal-attainment, Integration, Latency) yang merupakan bagian dari Teori Struktural Fungsional milik Talcott Parsons penelitian ini menghasilkan beberapa temuan. Berdasarkan pengumpulan data mengenai gelandangan dan pengemis yang ada di Kampung Topeng. Temuan-temuan penelitian ini menyatakan bentuk involusi pemberdayaan berupa ketidakberlanjutan program. Faktor-faktor penyebab involusi berasal dari pelaksanaan program dan warga binaan sasaran. Dari sisi pelaksana program terkait erat dengan perubahan skala prioritas program dinas, pergantian kepala dinas, keterbatasan sumber daya,  kemerosotan kolaborasi persoalan lokasi yang jauh dari pusat kota. Sedangkan dari sisi masyarakat kebudayaan kemiskinan dan kualitas tidak terstandar.